CHARACTERIZATION OF NORTHERN AND SOUTHERN ISOLATES OF TRICHINELLA IN IRAN - J. MASSOUD M. MAHDAVI (Tehran University of Medical Sciences, 1987)
Two isolates of Trichinella were obtained from the jackal, Canis aureus: one from the north Caspian area, the other from the south-west Khuzestan area of Iran. The infectivity of the isolates was tested in laboratory animals, in a wild rodent (Tatera indica) and in wild pigs. The isolate from Khuzestan was of low infectivity to albino rats and it was provisionally identified as Trichinella nelsoni. The Caspian isolate was highly infective for albino rats and wild pigs and was identified as Trichinella spiralis.